2021
DOI: 10.1002/int.22590
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing fusion of regularization techniques in the deep learning‐based intrusion detection system

Abstract: The surge of constantly evolving network attacks can be addressed by designing an effective and efficient Intrusion Detection System (IDS). Various Deep Learning (DL) techniques have been used for designing intelligent IDS. However, DL techniques face an issue of overfitting because of complex network structure and highdimensional data sets. Dropout and regularization are two competently perceived concepts of DL used for handling overfitting issue to enhance the performance of DL techniques. In this paper, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 75 publications
(191 reference statements)
0
5
0
Order By: Relevance
“…The highest accuracy achieved on CICIDS2017 dataset was 98.93% with XGboost. A fusion of regularization techniques is applied in [20], for increasing a DNN-based IDS performance, by using several datasets, including CICIDS2017.…”
Section: Related Workmentioning
confidence: 99%
“…The highest accuracy achieved on CICIDS2017 dataset was 98.93% with XGboost. A fusion of regularization techniques is applied in [20], for increasing a DNN-based IDS performance, by using several datasets, including CICIDS2017.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, researching and testing IDSs on incomplete datasets may yield inaccurate results [43], as shown in Ref. [44] in the case wherein these datasets are unbalanced. To address imbalance in training data, researchers focus on feature selection specifically, as in [43,45,46].…”
Section: Related Workmentioning
confidence: 99%
“…In UNSW-NB15, the network traffic is categorized into ten different types, including normal traffic, and nine attacks (e.g., fuzzers, analysis, backdoors, DoS, exploits, generic, reconnaissance, shellcode, and worms). In more detail, the normal traffic has 2,218,761 records and overwhelms attack traffic, which has 24,246,2677,2329,16,535,44,525,21,5481,13,987,1511, and 174 records for fuzzers, analysis, backdoors, DoS, exploits, generic, reconnaissance, shellcode, and worms, respectively.…”
Section: Experimental Datasets and Evaluation Metricmentioning
confidence: 99%
“…Shmalo et al 38 investigated the spectrum of weight layers using techniques from random matrix theory and determined that singular values should be removed during training to reduce overfitting and improve accuracy. To address overfitting issues encountered by deep learning techniques as a result of complex network structures, Thakkar et al 39 combined regularization and dropout effectively, improving the problem of deep learning overfitting. Some studies in other fields have reported that methods such as regularization 40,41 and data augmentation can alleviate the overfitting phenomenon to some extent.…”
Section: Introductionmentioning
confidence: 99%